Overexpression of a brassinosteroid biosynthetic gene Dwarf enhances photosynthetic capacity through activation of Calvin cycle enzymes in tomato. Issue 1 (December 2016) - Li, Xiao-Jing; Guo, Xie; Zhou, Yan-Hong; Shi, Kai; Zhou, Jie; Yu, Jing-Quan; Xia, Xiao-Jian
Abstract Background Genetic manipulation of brassinosteroid (BR) biosynthesis or signaling is a promising strategy to improve crop yield and quality. However, the relationships between the BR-promoted growth and photosynthesis and the exact mechanism of BR-regulated photosynthetic capacity are not clear. Here, we generated transgenic tomato plants by overexpressingDwarf, a BR biosynthetic gene that encodes the CYP85A1, and compared the photosynthetic capacity with the BR biosynthetic mutantd im and wild type. Results Overexpression ofDwarf promoted net photosynthetic rate (P N ), whereas BR deficiency ind im led to a significant inhibition inP N as compared with WT. The activation status of RuBisCO, and the protein content and activity of RuBisCO activase, but not the total content and transcripts of RuBisCO were closely related to the endogenous BR levels in different genotypes. However, endogenous BR positively regulated the expression and activity of fructose-1, 6-bisphosphatase.Dwarf overexpression enhanced the activity of dehydroascorbate reductase and glutathione reductase, leading to a reduced redox status, whereas BR deficiency had the contrasting effects. In addition, BR induced a reduction of 2-cystein peroxiredoxin without altering the protein content. Conclusions BR plays a role in the regulation of photosynthesis. BR can increase the photosynthetic capacity by inducing a reduced redox status that maintains the activation states of Calvin cycle enzymes.